A study on wear failure analysis of tungsten carbide hardfacing on carbon steel blade in a digester tank - Nagentrau, M.; Mohd Tobi, A. L.; Kamdi, Z.; Ismail, M. I.; Sambu, M. (Springer International Publishing, 2017)
This paper addresses wear failure analysis of tungsten carbide (WC) hardfacing on a carbon steel blade known as the continuous digester blade (CD blade). The CD blade was placed in a digester tank to mix ilmenite ore with sulphuric acid as part of a production process. Tungsten carbide hardfacing was applied on the CD blade to improve its wear resistance while the CD blade was exposed to an abrasive and acidic environment. Failure analysis was car-ried out on the hardfaced CD blade in order to improve its wear resistance and lifetime. A thickness and hardness comparison study was conducted on worn and unworn specimens from the CD blades. The carbide distribution along with elemental composition analysis of the hardfaced CD blade specimens was examined using scanning electron microscopy and energy-dispersive spectroscopy. The investigation revealed that an inconsistent hardfacing thickness was welded around the CD blade. Minimum coating thickness was found at the edges of the blade surfaces causing failure to the blades as the bare carbon steel blades were exposed to the mixed environment. The wear resistance of the CD blade can be improved by distributing the carbide uniformly on the hardfaced coating. Applying extra coating coverage at the critical edge will prevent the exposure of bare carbon steel blade, thus increasing the CD blade lifetime.